Effective English program for the technical school - Erickson, Harold (My University, 1968)
In the rapid growth of the Technical, vocational, and Adult Schools in Wisconsin, the technical subject areas have kept pace with the constantly changing demands of industry, while some of the academic areas, mainly English, have had little or no revision to meet these new demands. In spite of this fact, there has been a scarcity of research in evidence to show that any attempt has been made to bring the English programs abreast of the technical growth. For this reason, 379 questionnaires were sent to industries in Wisconsin, Iowa, and Minnesota to determine the English needs of the technician. In addition, 14 interviews were conducted with businesses in Wisconsin and Minnesota while the technical schools were asked to submit their English programs. These results were tabulated and mean percentages of time were found in order that an English program could be formed. The responses showed that between 57.2 and 69 per cent of the technician?s time is spent in communicative skills. They also revealed that technical reporting, a major portion of the job, was equally divided between oral and written reporting. As a result of the survey, a two semester English program for the technician was designed to meet the specific demands of industry.
Keywords: English language -- Technical English -- Study and teaching; English language -- Study and teaching (Higher)